Determinants of The Elderly Female Population with Low Economic Status in Indonesia - Ainistikmalia, Nurin (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2019)
Data from the Central Statistics Agency (2010) shows that more than half of the elderly population are elderly women. The results of studies and empirical studies also show that elderly women are vulnerable to various aspects of life, including poverty. This study aims to provide an overview of the condition of elderly women in Indonesia and determine the determinants/characteristics of the elderly female population with low economic status. The source of the data used comes from the Central Statistics Agency. The analytical methodology used is descriptive analysis and multiple regression analysis. The results show that the characteristics of elderly women in Indonesia are living with widowhood, lower education, more unemployed, and low health rates. In multiple regression analysis, it found that the variables of elderly women who do not work, the morbidity rate of elderly women, elderly women with widow status, elderly women with the status of head of household and elderly women who are illiterate simultaneously have an influence and can explain thevariables of elderly women with economic status. low at 51.3 percent. Keywords: Population Aging, Poverty, Economic Status, Elderly Women JEL: I30; P42